PENGEMBANGAN DESA KALIBAGOR BANYUMAS SEBAGAI DESA SENTRA WISATA KERAJINAN PAYUNG KERTAS TRADISIONAL - Arifin Suryo Nugroho; Ipong Jazimah; Wildan Nurul Fajar (Khazanah Pendidikan, 2020)
ABSTRACTKalibagor Village, Kalibagor District, Banyumas has the potential forcrafting paper umbrellas that have been passed down from generation togeneration. This partner village program aims to raise the potential for paperumbrella craft tourism in Kalibagor Village by preparing village resourcesthrough training and providing tools that support the promotion of KalibagorVillage as a paper umbrella craft Tourism Village. This activity lasted for 8months, involving 1 chief executive, 2 members, and the participation of UMPHistory Education students. The output program is in the form of scientificjournal articles, travel guides for paper umbrella crafts, and intellectualproperty rights in the form of copyrights.Keywords: tourism village, umbrella craft